Arun-III Project: Nepal’s Electricity Crisis and its Role in Current Load Shedding and Potential Role 10 Years Hence - Shrestha, Ratna Sansar (Hydro Nepal: Journal of Water, Energy and Environment, 2009)
It has become fashionable to blame ‘cancellation’ of the Arun-III hydroelectric project by the World Bank in 1995 in reference to Nepal’s current electricity crisis, inferring that had it been implemented consumers in Nepal would not be facing the current load shedding problem. Now is the time for a dispassionate and detached analysis of the two scenarios, with and without Arun-II I. The analysis of alternative scenarios demonstrates that implementation of the Arun-III 201 MW project in 1995 would not have eliminated load shedding from 2000 onwards; in fact, the power deficit may have been of a higher magnitude. Now, Arun-III planning is for a new incarnation with a capacity of 402 MW, expected to be completed within 10 years. But as the output of this project has been slated for export, it, too, will not alleviate the load shedding problem of Nepal.Hydro Nepal: Journal of Water, Energy and Environment Issue No. 4, January, 2009 Page 30-35